Transdisciplinary research and participatory action research in a decolonial key: Transdisciplinary research and participatory action research in a decolonial key - MERÇON, Juliana (Utopía y Praxis Latinoamericana, 2022)
Transdisciplinary research and participatory action research are fundamentally defined as theoretical-methodological proposals for the collaborative creation of knowledge and actions between diverse actors to transform social and environmental realities. In this article, I explore the main differences and convergences of these proposals, indicating their relationships with decolonial thinking and the epistemologies of the south. I end the text with a brief discussion of some ethical, political and epistemic conditions that favor transformative collaborative research processes.